2018
DOI: 10.3389/fphar.2018.00231
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Cisplatin-Induced Vomiting by Cannabis sativa in Pigeons: Neurochemical Evidences

Abstract: Cannabis sativa (CS, family Cannabinaceae) has been reported for its anti-emetic activity against cancer chemotherapy-induced emesis in animal models and in clinics. The current study was designed to investigate CS for potential effectiveness to attenuate cisplatin-induced vomiting in healthy pigeons and to study the impact on neurotransmitters involved centrally and peripherally in the act of vomiting. High-performance liquid chromatography system coupled with electrochemical detector was used for the quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Natural resources represent an important reservoir of bioactive compounds for the development of novel drug entities [13]. Among natural sources, the plants have been used to cure majority of the ailments since ancient times.…”
Section: Introductionmentioning
confidence: 99%
“…Natural resources represent an important reservoir of bioactive compounds for the development of novel drug entities [13]. Among natural sources, the plants have been used to cure majority of the ailments since ancient times.…”
Section: Introductionmentioning
confidence: 99%
“…* P < 0.05 vs. Group C, ‡ P < 0.05 vs. Group CG, † P < 0.05 vs. Group V, § P < 0.05 vs. Group M, || P < 0.05 vs. Group GL, ¶ P < 0.05 vs. Group GM. NEP neutral endopeptidase in dopamine, 5-HT and substance P receptors [42]. Endo et al [43] have suggested that 5-HT release from the enterochromaffin cells in ileum, accompanied by histopathological changes of the ileum mucosa, is involved in the onset of delayed emesis after administration of cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the content of the ADR, according to the standardised MedDRA Query (SMQ) ( MedDRA, 2018 ), the following ADRs: dependence, drug abuse, drug abuser, drug dependence, drug withdrawal convulsions, drug withdrawal syndrome, drug withdrawal neonatal syndrome, intentional product misuse, intentional product use issue, substance abuse, substance abuser, substance use and withdrawal syndrome were selected. Those ADRs were defined in accordance with MedDRA in line with previous studies on the EV dataset ( Chiappini et al, 2020 ; MedDRA, 2018 ; Schifano and Chiappini, 2018a , 2018b ; Schifano et al, 2019a , 2019b ). Specifically, abuse was here defined as the intentional, non-therapeutic use by a patient or consumer of a product, OTC or prescription, for a perceived reward or desired non-therapeutic effect including, but not limited to, getting high (euphoria) ( MedDRA, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…One of the limitations was given here by the descriptive nature of the study. Indeed, a comparator molecule, for a disproportionality analysis ( Chiappini and Schifano, 2016 ; Schifano and Chiappini, 2018b ) to be carried out, was not available due to data access limitations ( EMA, 2017 ; Postigo et al, 2018 ). Furthermore, current data did not appear to show an increasing trend of abuse or misuse across the years.…”
Section: Limitationsmentioning
confidence: 99%